Heterozygous FZ alpha 1 antitrypsin deficiency associated with severe emphysema and hepatic disease: case report and family study. Issue 9 (September 1989) - Kelly, C P; Tyrrell, D N; McDonald, G S; Whitehouse, D B; Prichard, J S
Abstract : A patient with advanced emphysema and cor pulmonale had the changes of alpha 1 antitrypsin deficiency in a liver biopsy specimen and was shown to have the phenotype PiFZ. This case supports the contention that the F allele of alpha 1 antitrypsin predisposes to the development of emphysema, particularly when it occurs in conjunction with the Z allele.